Flying blind? Recommendations for monitoring of 10 common chronic diseases in guidelines from Germany, England, and Europe — a modified systematic review - Koschemann, Victoria; Warkentin, Lisette; Viniol, Annika; Kühlein, Thomas; Hueber, Susann; Werner, Felix (BMC Medicine, 2025)
Background: Clinical practice guidelines (CPGs) synthesize evidence to recommend which measures should or should not be taken in specific medical situations and thereby inform and shape the practice of medicine. In the context of an ageing population, monitoring has become an increasingly resource-intensive practice, underscoring the need for clear, evidence-based guidance. Accordingly, this study aimed to investigate the level of detail as well as the level of evidence of recommendations on monitoring for 10 common chronic diseases in CPGs from the Association of the Scientific Medical Societies in Germany (AWMF), the National Institute for Health and Care Excellence (NICE), and European medical societies. Methods: Using a modified systematic review approach, a search of the relevant CPGs was conducted using the databases of the AWMF, NICE, and the Guidelines International Network (GIN). AWMF-equivalent evidence quality levels S2e and S3 CPGs were included. Recommendations on monitoring were extracted and evaluated, focusing on their level of detail regarding monitoring frequency, parameters, and consequences and their level of evidence, respectively. Results: A total of 29 CPGs were reviewed, and 163 recommendations on monitoring were extracted and evaluated. Recommendations provided a low level of detail regarding monitoring frequency in 34.4% of cases (n = 56), regarding parameters in 25.2% of cases (n = 41), and regarding consequences in 84.7% of cases (n = 138). A level of evidence was reported for 87 of 163 recommendations only, and if available, it was often low. Only a small proportion (6.7%; n = 11) of recommendations were formulated negatively as ‘do-not’ recommendations. Conclusions: The frequent lack of evidence or low level of evidence for monitoring recommendations, as well as the lack of detail in these recommendations, may lead to medical underuse, yet also to overuse, causing uncertainty among physicians and unnecessary diagnostic cascades. This has significant implications for patient harm, as well as financial and personnel burdens on the healthcare system. One potential solution could be the implementation of more ‘do-not’ recommendations in CPGs. However, overcoming systemic barriers is essential to enable the generation of high-quality evidence on monitoring.
CRIS-Team Scopus Importer:2025-12-12
Keywords: Clinical practice guidelines; Evidence-based medicine; Medical overuse; Monitoring